The short-term effect of a high protein, energy-dense oral liquid supplementation in nutritional status of patients with mild Alzheimer's disease - Sousa, Odete Luísa Vicente de (2007)
Abstract: Background The aetiology of weight loss in Alzheimer Disease (AD), has not yet been definitively established. Although appears multifactorial, a decline in food intake may be a contributor. Nutritional supplements are often prescribed, especially to prevention for weight loss, but it has not been demonstrated that a short-term nutritional supplementation has impact in AD-patients nutritional status. Objectives The aim of this study was (1) to evaluate the effect of short-term administration of a high protein, energy-dense Oral liquid Supplement (OS) in patients with mild AD who were malnourished, on nutritional status and in body composition, cognitive function and functional ability; (2) to assess the long-term effect of this intervention after discontinuation of the OS. Methods and Measurements A 21 days prospective randomized nonblinded controlled trial was conducted in a Geriatric Unit of a Psychiatric Hospital. From an initial group of Thirty five patients, twenty were randomly assigned to the Treatment Group (TG) n=20 and Fifteen to the Control Group (CG) n=15. During the study period, the TG received during 21 consecutive days, once a day a 200 mL high protein energy-dense OS, which provided 400kcal from a mixture of protein (18% of energy), fat (17.4% of energy), and carbohydrate (42.8% of energy) plus dietetic advice. Patients in the CG received the same dietetic advice as the TG, but no OS. The nutritional status, body composition, functional status and cognitive function were determined at baseline, 21 days (after intervention) and at 90 days of follow-up. The Mini Nutritional Assessment (MNA), anthropometric measurements, bioelectrical impedance analysis and serum biomarkers (albumin, total-protein, total-cholesterol, vitamin-B12 and folic acid) levels were obtained. Cognitive function was evaluated using the Mini Mental Status Examination (MMSE) tool and the Clock-Drawing Test (CDT). (...)